Use of prasugrel and clinical outcomes in African‐American patients treated with percutaneous coronary intervention for acute coronary syndromes. Issue 1 (17th January 2019) - Faggioni, Michela; Baber, Usman; Chandrasekhar, Jaya; Sartori, Samantha; Weintraub, William; Rao, Sunil V.; Vogel, Birgit; Claessen, Bimmer; Kini, Annapoorna; Effron, Mark; Ge, Zhen; Keller, Stuart; et al.
Abstract: Objective: To investigate the use of prasugrel after percutaneous coronary intervention (PCI) in African American (AA) patients presenting with acute coronary syndrome (ACS). Background: AA patients are at higher risk for adverse cardiovascular outcomes after PCI and may derive greater benefit from the use of potent antiplatelet therapy. Methods: Using the multicenter PROMETHEUS observational registry of ACS patients treated with PCI, we grouped patients by self‐reported AA or other races. Clinical outcomes at 90‐day and 1‐year included non‐fatal myocardial infarction (MI), major adverse cardiac events (composite of death, MI, stroke, or unplanned revascularization) and major bleeding. Results: The study population included 2, 125 (11%) AA and 17, 707 (89%) non‐AA patients. AA patients were younger, more often female (46% vs. 30%) with a higher prevalence of diabetes mellitus, chronic kidney disease, and prior coronary intervention than non‐AA patients. Although AA patients more often presented with troponin (+) ACS, prasugrel use was much less common in AA vs. non‐AA (11.9% vs. 21.4%, respectively, P = 0.001). In addition, the use of prasugrel increased with the severity of presentation in non‐AA but not in AA patients. Multivariable logistic regression showed AA race was an independent predictor of reduced use of prasugrel (0.42 [0.37–0.49], P < 0.0001). AA race was independently associated with a significantly higher risk of MI at 90‐days and 1 year after PCI. Conclusions: Despite higher risk clinical presentation and worse 1‐year ischemic outcomes, AA race was an independent predictor of lower prasugrel prescription in a contemporary population of ACS patients undergoing PCI.